Postprandial Hemodynamics in Hypertrophic Cardiomyopathy. Issue 11 (22nd May 2015) - Adams, Jonathon C.; Bois, John P.; Masaki, Mitsuru; Yuasa, Toshinori; Oh, Jae K.; Ommen, Steve R.; Nishimura, Rick A.; Klarich, Kyle W.
Abstract : Objectives: Prior analysis at our institution found that patients with hypertrophic cardiomyopathy (HCM) who experience postprandial symptoms (PPS) are more likely to have resting left ventricular outflow tract (LVOT) obstruction and reduced quality of life. Our objective was to determine whether PPS in patients with HCM vs healthy subjects occur as a result of measurable hemodynamic alterations in the postprandial hemodynamic response. Methods: We conducted a prospective cross‐sectional study examining 45 patients with HCM and 10 controls who underwent fasting and postprandial 2‐dimensional Doppler echocardiography. Postprandial echocardiographic measurements were obtained at symptom onset or 30 minutes after consumption of a standardized meal, whichever occurred first. Results: The HCM population included 18 (40%) patients with PPS and 27 (60%) without PPS. Compared to controls, mean resting peak LVOT gradient was 23.4 ± 17.6 mmHg in HCM patients with PPS and 25.1 ± 33.1 mmHg in those without PPS (P = 0.10). The mean change in peak LVOT gradient after a meal was 0.7 ± 1.1 mmHg for controls, 5.0 ± 8.3 mmHg for HCM patients with PPS, and 1.5 ± 18.2 mmHg for HCM patients without PPS (P = 0.64). Conclusion: Although the ability to provoke an increased LVOT gradient with a postprandial, upright exercise study protocol was recently reported, the current study suggests that a resting, supine, postprandial protocol does not elicit evidence of LVOT obstruction. Therefore, future investigations should consider whether simply performing an upright postprandial study in HCM patients with PPS will provide evidence of dynamic LVOT or if the addition of an exercise component is necessary.